PENGARUH FINNACIAL TECHNOLOGY DAN KEPUASAN NASABAH TERHADAP KINERJA KEUANGAN PERBANKAN PADA BANK NTT KUPANG (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2024)
The development of digital technology provides convenience and innovation in various sectors, including banking. Bank NTT, as part of the Indonesian banking industry, faces tight competition and strives to maintain customer trust through the implementation of Financial Technology (FinTech). This study aims to examine the influence of FinTech and customer satisfaction on the financial performance of Bank NTT. The results of the study are expected to provide insight for academics and banking practitioners in optimizing technological innovation to increase profitability and customer satisfaction. This study examines the financial performance of Bank NTT Kupang with a population of all bank customers. Primary data was collected through interviews and questionnaires, while secondary data was obtained from literature and official websites. The analysis involved descriptive statistics, classical assumption tests, multiple linear regression, and statistical tests. The results of this study indicate that (1) Financial Technology has a significant effect on Financial Performance; and (2) Customer Satisfaction has a significant effect on Banking Financial Performance. The results of this study are expected to provide a valuable contribution to Bank NTT so that it can create the latest innovations for banking products in the digital era to maintain customer satisfaction in improving banking financial performance.